Transcriptional activator Cat8 is involved in regulation of xylose alcoholic fermentation in the thermotolerant yeast Ogataea (Hansenula) polymorpha - Ruchala, Justyna (Microb Cell Fact, 2017)
BACKGROUND: Efficient xylose alcoholic fermentation is one of the key to a successful lignocellulosic ethanol production. However, regulation of this process in the native xylose-fermenting yeasts is poorly understood. In this work, we paid attention to the transcriptional factor Cat8 and its possible role in xylose alcoholic fermentation in Ogataea (Hansenula) polymorpha. In Saccharomyces cerevisiae, organism, which does not metabolize xylose, gene CAT8 encodes a Zn-cluster transcriptional activator necessary for expression of genes involved in gluconeogenesis, respiration, glyoxylic cycle and ethanol utilization. Xylose is a carbon source that could be fermented to ethanol and simultaneously could be used in gluconeogenesis for hexose synthesis. This potentially suggests involvement of CAT8 in xylose metabolism. RESULTS: Here, the role of CAT8 homolog in the natural xylose-fermenting thermotolerant yeast O. polymorpha was characterized. The CAT8 ortholog was identified in O. polymorpha genome and deleted both in the wild-type strain and in advanced ethanol producer from xylose. Constructed cat8Δ strain isolated from wild strain showed diminished growth on glycerol, ethanol and xylose as well as diminished respiration on the last substrate. At the same time, cat8Δ mutant isolated from the best available O. polymorpha ethanol producer showed only visible defect in growth on ethanol. CAT8 deletant was characterized by activated transcription of genes XYL3, DAS1 and RPE1 and slight increase in the activity of several enzymes involved in xylose metabolism and alcoholic fermentation. Ethanol production from xylose in cat8Δ mutants in the background of wild-type strain and the best available ethanol producer from xylose increased for 50 and 30%, respectively. The maximal titer of ethanol during xylose fermentation was 12.5 g ethanol/L at 45 °C. Deletion of CAT8 did not change ethanol production from glucose. Gene CAT8 was also overexpressed under control of the strong constitutive promoter GAP of glyceraldehyde-3-phosphate dehydrogenase. Corresponding strains showed drop in ethanol production in xylose medium whereas glucose alcoholic fermentation remained unchanged. Available data suggest on specific role of Cat8 in xylose alcoholic fermentation. CONCLUSIONS: The CAT8 gene is one of the first identified genes specifically involved in regulation of xylose alcoholic fermentation in the natural xylose-fermenting yeast O. polymorpha. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12934-017-0652-6) contains supplementary material, which is available to authorized users.